Podcast Sebagai Peluang Radio Elshinta Menambah Pendengar Dan Pendapatan - Haryo Ristamaji; Pitoyo Pitoyo (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Radio Elshinta is a national private radio station in Jakarta that carries the tagline "News And Talk" with programs containing news and information that are needed by its listeners. Radio Elshinta is the only radio station in Indonesia that only presents news without playing songs as its broadcast content. Along with the development of science and technology, new media or new media in the digital era has changed competition and the radio broadcasting industry. Competitors are not only from fellow radio stations, but from many digital platforms, so Radio Elshinta must innovate in order to maintain its existence as a radio media that presents news by increasing its listeners and income. This study uses a qualitative method based on Sekaran and Bougie (2016), organized, systematic, data-based, critical, objective business research, investigations or investigations into certain problems, carried out with the aim of finding answers or solutions. Data collection techniques were carried out by interviewing three key informants, namely the President Director, Marketing Coordinator and Advertising Agency. The results of this study indicate that in order to maintain its existence as a news radio in the era of disruption, Radio Elshinta must innovate in four steps. First, program innovation that is adjusted to the era of radio media disruption, Second, creating digital-based programs that are the tendency of society, Third, organizational transformation, Fourth, capital innovation, namely increasing capital by conducting cross media to target a wider market, and increasing human resources (HR).